Experimental and numerical studies on corrosion-resistant aluminium foam sandwich panel subject to low-velocity impact - Yuan, Jian; Liu, Kun; Gao, Cheng-Qiang; You, Zhi-Yue; Kang, Shao-Bo (Scientific reports, 2024)
Aluminium foam sandwich panels (AFSPs) have a high impact resistance and are suitable for a wide range of engineering applications. To improve corrosion resistance, this paper proposes an anti-corrosion sandwich panel with stainless steel as the upper sheet. Drop hammer impact tests were performed on a total of ten AFSPs to investigate their dynamic response and failure patterns. To assess the deformation performance of AFSPs, a laser displacement meter was used to obtain the bottom centre displacement. The effects of the impact energy and the thickness of each component of AFSPs on the peak impact force and deformation performance were studied. Test results showed that the thickness of each component had notable effects on the impactor and bottom displacements. In addition, the effect of the unit mass of the components in AFSPs on decreasing the bottom displacement was discussed. Compared to increasing the aluminium foam and lower sheet thicknesses, increasing the upper sheet thickness was more effective in decreasing the bottom displacement. A finite element model of AFSPs was developed to conduct parameter analysis, indicating that impactors with larger diameters resulted in higher peak forces and reduced deformation of AFSPs.